The development of tragedy as a genre (Texas Journal of Philology, Culture and History, 2023)
This article talks about the fact that the genre of tragedy in Karakalpak dramaturgy was created on the basis of world experience, and about the skill of the playwrights to use in their own experience through the deep assimilation of classic works of Russian and European countries in tragedies.